Antenatal venous thromboembolism. (20th June 2021) - Crosby, David A; McHugh, Ann; Ryan, Kevin; Byrne, Bridgette
Abstract : Key content: Venous thromboembolism (VTE) remains one of the leading causes of maternal mortality and morbidity in the developed world. Clinical diagnosis of antenatal VTE is difficult and scoring systems have historically been of limited benefit in the pregnant population. However, evidence is emerging to suggest that pregnant women can be risk stratified for pulmonary embolism without the need for imaging in all cases. Optimal treatment is with weight adjusted therapeutic dose low‐molecular‐weight heparin (LMWH) subcutaneously. In rare cases, there may be a role for retrievable inferior vena cava (IVC) filters. The obstetrician has a key role in the multidisciplinary team discussion with the aim of minimising maternal risk of haemorrhage or thrombosis. Learning Objectives: To understand the optimal approach to diagnosing VTE in pregnancy and the antenatal management of acute VTE. To understand the rare indications, risks and benefits of IVC filters in pregnancy. To understand the complexity of decision making around the time of delivery to minimise the risk of bleeding and recurrent thrombosis.